2017
DOI: 10.1371/journal.pone.0188497
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone length, growth plate thickness, bone content, and IGF-I as a model for poor growth in the CFTR-deficient rat

Abstract: BackgroundReduced growth and osteopenia are common in individuals with cystic fibrosis (CF). Additionally, improved weight and height are associated with better lung function and overall health in the disease. Mechanisms for this reduction in growth are not understood. We utilized a new CFTR knockout rat to evaluate growth in young CF animals, via femur length, microarchitecture of bone and growth plate, as well as serum IGF-I concentrations.MethodsFemur length was measured in wild-type (WT) and SD-CFTRtm1sage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
2
13
0
1
Order By: Relevance
“…CFTR G542X knockin rats demonstrated severe CF manifestations and developmental defects. CF-related abnormalities included reduced growth, aberrant tooth enamel, and meconium ileus ( Figure 1 ), similar to observations in CF rodent models and patients ( Wright et al, 1996 ; Arquitt et al, 2002 ; Meyerholz et al, 2010 ; Tuggle et al, 2014 ; Stalvey et al, 2017 ). Reduced CFTR expression and activity was evident in multiple organs ( Figures 2–4 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…CFTR G542X knockin rats demonstrated severe CF manifestations and developmental defects. CF-related abnormalities included reduced growth, aberrant tooth enamel, and meconium ileus ( Figure 1 ), similar to observations in CF rodent models and patients ( Wright et al, 1996 ; Arquitt et al, 2002 ; Meyerholz et al, 2010 ; Tuggle et al, 2014 ; Stalvey et al, 2017 ). Reduced CFTR expression and activity was evident in multiple organs ( Figures 2–4 ).…”
Section: Discussionsupporting
confidence: 78%
“…CFTR G542X rats displayed development-associated consequences similar to those seen in CFTR knockout rats ( Tuggle et al, 2014 ; Stalvey et al, 2017 ). Marked growth retardation in homozygous rats was observed after 21 days of age, although body sizes between groups appeared similar at birth.…”
Section: Resultsmentioning
confidence: 80%
“…While CF rats do not spontaneously develop lung or pancreatic disease during their first 6-weeks of life, they are a good model for investigating bone growth and its direct link to CFTR, without the presence of other disease manifestations such as airway disease. Accordingly, Stalvey et al (2017) examined the role of CFTR loss on bone growth using young Cftr -/- rats by measuring their femur length, bone histomorphometry and cartilaginous growth plates as well as the concentration of serum IGF-I. Deficiency in IGF-I can cause changes in cartilage growth.…”
Section: Lung and Intestine Observations In A Recent Cystic Fibrosis mentioning
confidence: 99%
“…They found that in absence of the CFTR gene, rats show reduced growth and bone content. Also, IGF-I concentration in the serum of Cftr -/- rats (a marker also used in non-CF children with bone disease) is decreased, which may explain changes in the growth plate (Stalvey et al, 2017).…”
Section: Lung and Intestine Observations In A Recent Cystic Fibrosis mentioning
confidence: 99%
“… 2018 ), reduced growth plate thickness (Stalvey et al. 2017 ), and increased cortical porosity (Osima et al. 2017 ) support the incidence of compromised bone quality in diabetic subjects.…”
Section: Introductionmentioning
confidence: 96%